Implementasi Metode Design Thinking Dalam Perancangan UI/UX Design Pada Website IT Asset Management - Muhamad Fikri; Anna Mukhayaroh (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Bina Insani, 2026)
Effective IT asset management is crucial for maintaining work efficiency. Previously, asset recording was done manually using Google Forms, which often led to issues such as incomplete data, inconsistent formats, and difficulty in double-checking device specifications. This study used the Design Thinking method, which includes the stages of Empathize, Define, Ideate, Prototype, and Test, to design the UI/UX of a web-based IT Asset Management system. The System Usability Scale (SUS) test results obtained a score of 87, with a Grade A category, indicating excellent system usability. This system is expected to facilitate the recording, reporting, and management of IT assets in a more structured and efficient manner.